The Third Transmembrane Domain of EscR Is Critical for Function of the Enteropathogenic Escherichia coli Type III Secretion System - Irit Tseytin (American Society for Microbiology, 2018)
ABSTRACT Many Gram-negative bacterial pathogens utilize a specialized protein delivery system, called the type III secretion system (T3SS), to translocate effector proteins into the host cells. The translocated effectors are crucial for bacterial infection and survival. The base of the T3SS transverses both bacterial membranes and contains an export apparatus that comprises five membrane proteins. Here, we study the export apparatus of enteropathogenic Escherichia coli (EPEC) and characterize its central component, called the EscR protein. We found that the third transmembrane domain (TMD) of EscR mediates strong self-oligomerization in an isolated genetic reporter system. Replacing this TMD sequence with an alternative hydrophobic sequence within the full-length protein resulted in a complete loss of function of the T3SS, further suggesting that the EscR TMD3 sequence has another functional role in addition to its role as a membrane anchor. Moreover, we found that an aspartic acid residue, located at the core of EscR TMD3, is important for the oligomerization propensity of TMD3 and that a point mutation of this residue within the full-length protein abolishes the T3SS activity and the ability of the bacteria to translocate effectors into host cells. IMPORTANCE Many Gram-negative bacterial pathogens that cause life-threatening diseases employ a type III secretion system (T3SS) for their virulence. The T3SS comprises several proteins that assemble into a syringe-like structure dedicated to the injection of bacterial virulence factors into the host cells. Although many T3SS proteins are transmembrane proteins, our knowledge of these proteins is limited mostly to their soluble domains. In this study, we found that the third transmembrane domain (TMD) of EscR, a central protein of the T3SS in enteropathogenic E. coli, contributes to protein self-oligomerization. Moreover, we demonstrated that a single aspartic acid residue, located at the core of this TMD, is critical for the activity of the full-length protein and the function of the entire T3SS, possibly due to its involvement in mediating TMD-TMD interactions. Our findings should encourage the mapping of the entire interactome of the T3SS components, including interactions mediated through their TMDs.